The thermophysical properties of metallic liquids. Volume 2, - Iida, Takamichi; Guthrie, Roderick I. L. (Oxford University Press, 2015)
This volume considers the essential conditions for a model to be truly predictive. The authors use a statistical approach to rate the validity of the various predictive models that have been previously used for evaluating various thermophysical properties. On the basis of this assessment, the authors have predicted values for the thermophysical properties of elemental metallic liquids, which are lacking in experimental data.
Keywords: Liquid metals -- Thermal properties -- Computer simulation.; Liquid metals -- Effect of temperature on -- Computer simulation.; elektronické knihy; electronic books